Weekend effect on mortality by medical specialty in six secondary hospitals in the Helsinki metropolitan area over a 14-year period - Morag Tolvi; Kimmo Mattila; Jari Haukka; Leena-Maija Aaltonen; Lasse Lehtonen (BMC, 2020)
Abstract Background The weekend effect is the phenomenon of a patient's day of admission affecting their risk for mortality. Our study reviews the situation at six secondary hospitals in the greater Helsinki area over a 14-year period by specialty, in order to examine the effect of centralization of services on the weekend effect. Methods Of the 28,591,840 patient visits from the years 2000-2013 in our hospital district, we extracted in-patients treated only in secondary hospitals who died during their hospital stay or within 30 days of discharge. We categorized patients based on the type of each admission, namely elective versus emergency, and according to the specialty of their clinical service provider and main diagnosis. Results A total of 456,676 in-patients (292,399 emergency in-patients) were included in the study, with 17,231 deaths in-hospital or within 30 days of discharge. A statistically significant weekend effect was observed for in-hospital and 30-day post-discharge mortality among emergency patients for 1 of 7 specialties. For elective patients, a statistically significant weekend effect was visible in in-hospital mortality for 4 of 8 specialties and in 30-day post-discharge mortality for 3 of 8 specialties. Surgery, internal medicine, and gynecology and obstetrics were most susceptible to this phenomenon. Conclusions A weekend effect was present for the majority of specialties for elective patients, indicating a need for guidelines for these admissions. More disease-specific research is necessary to find the diagnoses, which suffer most from the weekend effect and adjust staffing accordingly.